BAKTI SOSIAL HISFARMA DAN PERSIT KCK HUBDAM I/BBU HIMPUNAN SEMINAT FARMASI MASYARAKAT PD IAI SUMATRA UTARA - Manahan Situmorang; Dumartina Hutahuruk; Jon Kenedy Marpaung; Siti Nurbaya; Natanael Priltius (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2022)
Blood donation activity is the obligation of every community as a form of concern for others. Many people do not know about the health benefits of blood donation. There are even people who are reluctant to donate blood because they are worried about the side effects it causes. In fact, by donating blood, the blood cells in the body are replaced more quickly with new ones. The purpose of this activity was to carry out the HISFARMA Social Service and Persit KCK HUBDAM I/BBU Community Pharmacy Seminate Association PD IAI North Sumatra. This activity was carried out by conducting a site survey with the implementation team, meeting with Representatives of PERSIT KCK HUBDAM I/BBU, Medan, North Sumatra. This activity was opened by the presenter, after that singing the Indonesia Raya anthem, welcoming remarks, followed by blood donation activities, blood sugar checks, a careful echo talk show and ended with a group photo. Implementation of community service in the form of social services in educating the public on the importance of blood donation, blood sugar checks and careful echo talk shows. Health Checkup has many benefits. When donating blood, the blood cells in the body are replaced more quickly with new ones. If you donate blood once every three months, your body will stay healthy. Besides being useful for helping others, blood donation also makes our bodies healthier. So it can be concluded that this activity has a good impact and influence on people's knowledge in carrying out this activity.